Transvaal and Natal Iron Age settlement revealed by aerial photography and excavation - Mason, R.J (My University, 1968)
In 1820 John Campbell visited a thriving Iron Age settlement built by the Hurutse tribe at that time under the regent Liqueling, and known as Kurrichane or Kaditshwene (spelling uncertain), believed to be near the present town of Zeerust in the S.W. Transvaal. … In 1828 Robert Moffat, travelling to the east of Kurrichane, described remains of innumerable, recently destroyed settlements similar to Kurrichane. Moffat’s record was the start of Iron Age research in the Transvaal. Most, or all, of the Iron Age structures discussed in the present paper probably predate the tribal wars of the 1820's. My subject in the present paper is confined to Iron Age structures.
African Studies Seminar series. Paper presented 1968
Keywords: Aerial photography in archaeology; Excavations (Archaeology). South Africa; Iron age. South Africa; Venda (African people); Transvaal. Antiquities; Natal. Antiquities